2013
DOI: 10.1377/hlthaff.2013.0613
|View full text |Cite
|
Sign up to set email alerts
|

Hospitals With Higher Nurse Staffing Had Lower Odds Of Readmissions Penalties Than Hospitals With Lower Staffing

Abstract: The Affordable Care Act’s Hospital Readmissions Reduction Program (HRRP) penalizes hospitals based on excess readmission rates among Medicare beneficiaries. The aim of the program is to reduce readmissions while aligning hospitals’ financial incentives with payers’ and patients’ quality goals. Many evidence-based interventions that reduce readmissions, such as discharge preparation, care coordination, and patient education, are grounded in the fundamentals of basic nursing care. Yet inadequate staffing can hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
107
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 30 publications
5
107
1
1
Order By: Relevance
“…Our findings add to the growing body of literature that demonstrates a relationship between readmissions and the working conditions of nurses 43. Recent studies have suggested that hospitals may experience fewer CMS readmission penalties by increasing financial resources devoted to nursing care 43.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our findings add to the growing body of literature that demonstrates a relationship between readmissions and the working conditions of nurses 43. Recent studies have suggested that hospitals may experience fewer CMS readmission penalties by increasing financial resources devoted to nursing care 43.…”
Section: Discussionsupporting
confidence: 58%
“…Recent studies have suggested that hospitals may experience fewer CMS readmission penalties by increasing financial resources devoted to nursing care 43. Others have found that the cost of such investments is offset by the return in savings due to reduced 30-day readmissions and postdischarge emergency department visits 11…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] The US studies have generally concluded that a hospital skill mix with proportionately more professional nurses yields greater value because higher wages of professional nurses are offset by reductions in length of stay, lower use of intensive care, fewer costly adverse events such as hospital-acquired infections and lower readmission rates. [25][26][27][28][29] Needleman et al estimated that holding constant the total number of hours of nursing care provided, replacing lower qualified licensed practical nurses with fewer years of education with professional nurses would result in lower hospital mortality, shorter length of stay, fewer complications and net savings. 30 The aim of this paper is to inform managerial and policy decision-making about hospital nursing skill mix in Europe through an analysis of the association between nursing skill mix and patient mortality, patient ratings of their care and quality of care indicators in hospitals in six European countries: Belgium, England, Finland, Ireland, Spain and Switzerland.…”
Section: Introductionmentioning
confidence: 99%
“…13 Hospitals with better nurse staffing were 25% less likely to be penalized under the HRRP. 14 One study on surgical readmissions of Medicare patients included a measure of nurse staffing (which was significantly associated), but this finding was not discussed. 15 Other hospital nursing factors shown to be predictive of patient outcomes, such as work environment, were rarely considered.…”
Section: Introductionmentioning
confidence: 99%